IoT Smart Laboratory Trainer Based on Raspberry Pi as Education for Electrical Engineering Students at Telecommunication Laboratory, Surabaya State University - Oka, Hikmat; Kholis, Nur; Nusriningyati, Nusriningyati; Rosyidi, Rokhis (Proceeding of International Joint Conference on UNESA, 2024)
In order to carry out the process of learning and teaching at the Telecommunications Laboratory in Universitas Negeri Surabaya, efforts to increase student learning efficiency in the field of telecommunications must be preserved, and for that particular reason creating learning media in the form of an IoT-based smart laboratory trainer kit using a Raspberry Pi is expected to increase learning efficiency. The aim is that students can learn to make IoT-based smart laboratory applications with simple sensors and actuators as a simplification in real-world applications. The students will increase their understanding of the material exponentially and will greatly support student competence before entering the workplace. This study used Research and Development (R&D) method by creating a learning media prototype. The steps taken are media design, tool design, software-hardware integration, and the final step is tool validation. The result of this study is an IoT-based smart laboratory trainer kit with excellent validation value as proof that the tool is suitable as a learning medium.